The improvement of elderly sleeping quality with progressive muscle relaxation therapy - Apriyeni, Emira; Patricia, Helena (International Journal Of Community Medicine And Public Health, 2020)
Background: Sleep is one part of physiological needs and it is a basic need which is needed by all humans to be able to function optimally. However, the elderly will often experience sleep disorders. Sleep disorders in the elderly will affect the quality of sleep. One of nursing intervention that can improve the elderly sleeping quality is progressive muscle relaxation therapy. This study aims to determine the differences of sleep quality before and after having progressive muscle relaxation therapy toward the elderly with sleep disorders. Methods: This research was conducted at the Tresna Werdha Sabai Nan Aluih Social Home, Sicincin in 2019. The research was conducted for 2 weeks with one-week intervention. This research is a Quasy experiment using one group pre-test and post-test without control group design approach. This study used the sample of 16 respondents taken by purposive sampling. The analysis of data uses dependent T-test with a significance level of 95% (α 0.05). Results: The results of the study found that the average sleep quality of the elderly before being given the intervention was 13.63 and after the intervention it became 8.44 with p value of 0.000. Conclusions: The results showed that there were significant differences before and after the intervention. For this reason, it is recommended for the elderly with sleep disorders to be able to do progressive muscle relaxation therapy to improve sleep quality.